1999
DOI: 10.1074/jbc.274.48.34196
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Human MBF1 as a Transcriptional Coactivator

Abstract: Multiprotein bridging factor 1 (MBF1) is a coactivator which mediates transcriptional activation by interconnecting the general transcription factor TATA elementbinding protein and gene-specific activators such as the Drosophila nuclear receptor FTZ-F1 or the yeast basic leucine zipper protein GCN4. The human homolog of MBF1 (hMBF1) has been identified but its function, especially in transcription, remains unclear. Here we report the cDNA cloning and functional analysis of hMBF1. Two isoforms, which we term hM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
65
1
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(70 citation statements)
references
References 26 publications
2
65
1
1
Order By: Relevance
“…The CpMBF1 transcription level is low in free sporozoites and intracellular parasites during their early invasion stages, and CpMBF1 protein is barely detectable in intact oocysts and free sporozoites, suggesting that CpMBF1 may play a role in activating certain genes during the intracellular development of C. parvum. In addition to the activation of histidine synthetic genes in yeast under histidine starvation, MBF1-mediated pathways are known to cause cell differentiation in insects, the formation of stalks in the slime mould Dictyostelium discoideum and the differentiation of endothelial cells in mammals (Dragoni et al, 1998;Kabe et al, 1999;Singleton et al, 1991;Takemaru et al, 1997). These observations, together with the parasite life cycle stage-dependent expression pattern, imply that CpMBF1 may be involved in the cell differentiation of C. parvum during its complex life cycle.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…The CpMBF1 transcription level is low in free sporozoites and intracellular parasites during their early invasion stages, and CpMBF1 protein is barely detectable in intact oocysts and free sporozoites, suggesting that CpMBF1 may play a role in activating certain genes during the intracellular development of C. parvum. In addition to the activation of histidine synthetic genes in yeast under histidine starvation, MBF1-mediated pathways are known to cause cell differentiation in insects, the formation of stalks in the slime mould Dictyostelium discoideum and the differentiation of endothelial cells in mammals (Dragoni et al, 1998;Kabe et al, 1999;Singleton et al, 1991;Takemaru et al, 1997). These observations, together with the parasite life cycle stage-dependent expression pattern, imply that CpMBF1 may be involved in the cell differentiation of C. parvum during its complex life cycle.…”
Section: Discussionmentioning
confidence: 75%
“…Drosophila nuclear receptor FTZ-F1 or yeast leucine zipper protein GCN4) (Dragoni et al, 1998;Kabe et al, 1999;Li et al, 1994;Liu et al, 2003;Takemaru et al, 1997Takemaru et al, , 1998. We have previously identified its C. parvum counterpart and demonstrated that the CpMBF1 gene is able to functionally complement MBF1 deficiency in yeast (Zhu et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, the MBF1 homologues factors were identified in yeast, parasites, and humans (Takemaru et al, 1997;Kabe et al, 1999;Zhu et al, 2000). Takemaru et al (1997) and Kabe et al (1999) found that yeast and human MBF1 bind to different transcription factors of the basic leucine zipper (bZip) family, including yeast GCN4, bovine Ad4BP/SF1, and human ATF1, c-Jun, and c-Fos. Godoy et al, (2001) isolated and characterized a potato (Solanum tuberosum) cDNA clone that encodes a protein (StMBF1) with high sequence homology with human, yeast, and Bombix mori MBF1.…”
Section: Introductionmentioning
confidence: 99%
“…The multiprotein bridging factor 1 (MBF1) was originally purified from extracts of the silkworm Bombyx mori and identified as a transcriptional co-activator that interacts with the general transcription factor TBP (TATA box binding protein) and the Drosophila melanogaster nuclear receptor FTZ-F1 (Li et al, 1994). Later, the MBF1 homologues factors were identified in yeast, parasites, and humans (Takemaru et al, 1997;Kabe et al, 1999;Zhu et al, 2000). Takemaru et al (1997) and Kabe et al (1999) found that yeast and human MBF1 bind to different transcription factors of the basic leucine zipper (bZip) family, including yeast GCN4, bovine Ad4BP/SF1, and human ATF1, c-Jun, and c-Fos.…”
Section: Introductionmentioning
confidence: 99%